Wear resistance of nano-polycrystalline diamond with various hexagonal diamond contents - Kurio, A.; Tanaka, Y.; Sumiya, H.; Irifune, T.; Shinmei, T.; Ohfuji, H.; Kagi, H. (Сверхтвердые материалы, 2012)
Wear resistance of nano-polycrystalline diamond (NPD) rods containing various amounts of hexagonal diamond has been tested with a new method for practical evaluation of the wear–resistance rate of superhard ceramics, in addition to the measurements of their Knoop hardness. The wear resistance of NPD has been found to increase with increasing synthesis temperature and accordingly decreasing proportion of hexagonal diamond. A slight increase in Knoop hardness with the synthesis temperature also has been observed for these samples, consistent with the results of the wear–resistance measurements. These results suggest that the presence of hexagonal diamond would not yield any observable increase in both hardness and wear resistance of NPD, contradictory to a recent prediction suggesting that hexagonal diamond is harder than cubic diamond. It is also demonstrated that NPD is superior to single crystal diamond in terms of relatively homogeneous wearing without any significant chipping/cracking. Зносостійкість нано-полікристалічних алмазних (НПА) стрижнів, з різним вмістом гексагонального алмазу, була протестована новим методом практичної оцінки швидкості зносу надтвердої кераміки, додатково до вимірюваня їх твердості по Кнупу. Було виявлено, що зносостійкість НПА збільшується зі зростанням температури синтезу і, відповідно, зі зменшенням частки гексагональних алмазів. Також, відповідно до результатів вимірювань зносостійкості, для цих зразків спостерігалося невелике збільшення твердості по Кнупу з температурою синтезу. Ці результати дозволяють припустити, що присутність гексагональних алмазів не приводить до будь-якого помітного збільшення як твердості, так і зносостійкості НПА, що суперечить недавньому припущенню про те, що гексагональний алмаз твердіший, ніж кубічний. Також показано, що НПА перевершує монокристал алмазу з точки зору відносно однорідного зношування без значних відколів/тріщин. Износостойкость нано-поликристаллических алмазных (НПА) стержней, с различным содержанием гексагонального алмаза, была протестирована новым методом практической оценки скорости износа сверхтвердой керамики, в дополнение к измерениям их твердости по Кнупу. Было обнаружено, что износостойкость НПА увеличивается с ростом температуры синтеза и, соответственно, с уменьшением доли гексагональных алмазов. Также, в соответствии с результатами измерений износостойкости, для этих образцов наблюдалось небольшое увеличение твердости по Кнупу с температурой синтеза. Эти результаты позволяют предположить, что присутствие гексагональных алмазов не приводит к какому-либо заметному увеличению как твердости, так и износостойкости НПА, что противоречит недавнему предположению о том, что гексагональный алмаз тверже, чем кубический. Также показано, что НПА превосходит монокристалл алмаза с точки зрения относительно однородного изнашивания без значительных сколов/трещин.